Molecular biology - Weaver, Robert F.; Weaver, Robert F. (New York, Mc Graw Hill, 2012)
Molecular Biology, 5/e by Robert Weaver, is designed for an introductory course in molecular biology. Molecular Biology 5/e focuses on the fundamental concepts of molecular biology emphasizing experimentation. In particular author, Rob Weaver, focuses on the study of genes and their activities at the molecular level. Through the combination of excellent illustrations and clear, succinct writing students are presented fundamental molecular biology concepts.
Glossary 827-855p.; Index 856-892p.
Keywords: Genomes; Translation; Molecular biology